2018
DOI: 10.1063/1.5011953
|View full text |Cite
|
Sign up to set email alerts
|

Controlled electromigration protocol revised

Abstract: Electromigration has evolved from an important cause of failure in electronic devices to an appealing method, capable of modifying the material properties and geometry of nanodevices. Although this technique has been successfully used by researchers to investigate low dimensional systems and nanoscale objects, its low controllability remains a serious limitation. This is in part due to the inherent stochastic nature of the process, but also due to the inappropriate identification of the relevant control parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…depending on the thermal conductivity, specific heat, heat transfer to the substrate and sample geometry as well. From this expression, the following relation can be deduced [19]…”
Section: Estimation Of the Local Temperature At The Constrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…depending on the thermal conductivity, specific heat, heat transfer to the substrate and sample geometry as well. From this expression, the following relation can be deduced [19]…”
Section: Estimation Of the Local Temperature At The Constrictionmentioning
confidence: 99%
“…In addition, recent works also showed that the change of electrical resistance in random networks of conducting nanowires under electric bias can induce percolation in these materials, making them interesting transparent conducting materials suitable in a wide range of applications, as window electrodes, transparent heaters, antennas, etc [13,14]. Besides this rich multipurpose nanofabrication toolbox, controlled EM benefits from the fact that it can be achieved through rather unsophisticated softwares and conventional electronics [6,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…To produce a nanogap at the narrowest point in the bow-tie structure, we use the EM technique, which is able to surpass the resolution limitations of contemporary lithography methods 11 . Hereto, we applied a novel EM protocol that was demonstrated to have a high controllability and reproducibility 48 . The successful creation of a few atom bridge between the two contacts is reflected in the quantization of the conductance 25 , which is continuously monitored during EM (see Fig.…”
Section: Nano-separated Electrical Contactsmentioning
confidence: 99%
“…The model is fit by minimizing the sum of squared residuals between the measured (I c ) and predicted (I ĉ ) critical currents for all the EM onset points in a trace, where Figure 3(b) illustrates fitting this model to EM onset points for a set of devices at different environmental temperatures. The precise voltage points depend on what EM speed is considered to be true onset [27], but in practice ignoring this consideration does not significantly alter the onset points. Because of the strong positive feedback in both current density and heat dissipation in the junction as it narrows, EM at the nanoscale is a strongly activated process: negligible below some threshold voltage and rapidly accelerating beyond that voltage.…”
Section: Constant Critical Power Modelmentioning
confidence: 99%